(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Workplace wellness practices focus on lowering employee risk by providing ongoing health promotion and sickness management because they allow for frequent contact with employees through regulated environmental and communication systems, workplaces are perfect for health behaviour change. Here the researchers tried to understand the employee’s perception towards wellness practice, check the employees’ interest in different wellness practice and recommended to implement employee wellness measures in the company. A substantial amount of material was obtained and then combined and concentrated in an ethical manner in order to partially satisfy the requirements for the academic research project. This project was conducted in order to meet a component of those specifications. Apart from the guide and his student, researchers provided significant contributions to this study work, which served to make it more realistic.